The Effectiveness of Foot SPA on the Intensity of Labor Pain in the Active Phase of First Stage at BPM Ani Karawang - Nita Talia (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Foot SPA is a treatment for the Making Pregnancy Saver (MPS) program to nourish the skin on the feet, relieve fatigue or as a relaxation technique, and reduce swelling of the feet. The aim of this community service is to determine the effect of the effectiveness of foot SPA on the intensity of labor pain in the active phase of the first stage at BPM Midwife Ani Karawang. The method is a type of experimental community service in the form of Pre-Experimental Designs. The community service design is One Group Pretest-Posttest Design. The population in this study was 60 mothers giving birth. The sampling technique is purposive sampling. The samples in this study were 38 samples according to the criteria. Data analysis used univariate analysis and bivariate analysis with the Wilcoxon Signed Ranks Test. The results of community service from 38 respondents showed that the percentage of labor pain intensity in the first active phase before the foot SPA was carried out at BPM Midwife Ani Karawang was 78.9% (severe pain). The percentage of intensity of labor pain in the first active phase after a foot SPA was performed at BPM Midwife Ani Karawang was 71.1% (moderate pain). The Wilcoxon Asymp.Sig (2-tailed) test value is 0.000, so H0 fails to be rejected, meaning that foot SPA is effective on the intensity of labor pain during the first active phase at BPM Midwife Ani Karawang. In conclusion, foot SPA is effective for the intensity of labor pain in the active phase of the first stage at BPM Midwife Ani Karawang.